Guide for the Realization of Tests and Classification of Asphalt, Asphalt Emulsions and Asphalt Cutback According to the Central American Technical Regulation (RTCA 75.01.22: 047) - Salazar Delgado, Jorge (2025)
This document presents a summary and description of the RTCA 75.01.22:047 as a guide to characterize and classify asphalt binders un-modified, conventional asphalt, asphalt emulsions and cutback asphalt, required to provide the minimum specifications to be used in rehabilitation , reconstruction and construction of roads. This article is addressed mainly to companies and testing laboratories related to the road sector that require determining the quality of materials used in the processes of maintenance, rehabilitation or reconstruction, in addition is a description or interpretation of the results of each test.